1998
DOI: 10.1017/s1355617798466074
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive speed in nondemented Parkinson's disease

Abstract: Studies of speed of cognitive processing in Parkinson's disease (PD) have yielded mixed results. This may relate in part to a differential effect on cognitive speed by the type of information to be processed. In the present study, we compared medication fasted, nondemented individuals with mild idiopathic PD (N 5 26) with age-matched controls (N 5 12) on a test requiring easy and hard same-different discriminations for verbal, quantitative, and spatial information, as well as on a traditional memory scanning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…For this later group, only those times-of-assessment where PD was diagnosed were included. Thus PD patients reported here are a subset of a larger clinical cohort reported previously 1,2,4,5,12 with the important distinction of having been assessed at least 3 times so changepoint models have sufficient repeated measures data to be estimated. Thus all PD participants enrolled without cognitive impairment (i.e., CDR 0); and there were sufficient number of repeated measures to estimate MRC change points.…”
Section: Methodsmentioning
confidence: 99%
“…For this later group, only those times-of-assessment where PD was diagnosed were included. Thus PD patients reported here are a subset of a larger clinical cohort reported previously 1,2,4,5,12 with the important distinction of having been assessed at least 3 times so changepoint models have sufficient repeated measures data to be estimated. Thus all PD participants enrolled without cognitive impairment (i.e., CDR 0); and there were sufficient number of repeated measures to estimate MRC change points.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the finding of reduced cognitive speed may very well have been caused by the inclusion of patients with mild dementia or depression (Smith, 1998). For an excellent and comprehensive review of the literature on cognitive deficits in PD, one is advised to read the chapter by Pillon and co-workers in the recent Handbook of Neuropsychology (Pillon, 2001).…”
Section: Cognitive Deficits In Non-demented Pd Patientsmentioning
confidence: 99%
“…Using the SIRP, Smith and colleagues did not find slowing of the motor component of the response time in a group of dopaminergically depleted patients with Parkinson's disease. 24 Specific task characteristics, including the type of motor response required (for example button press, as in the current study, versus a response that requires a larger movement) may provide a partial explanation of these contrasting findings. 38 In addition, although the motor component of the SIRP is conceptually similar to simple response time, it differs in that it is a derived measure (the y intercept of the regression line) that isolates the motor component of response time.…”
Section: Discussionmentioning
confidence: 71%
“…[22][23][24] The SIRP is a choice-reaction time test that dissociates the motor and cognitive components of response time. Accurate responses are predicated upon a temporarily stored representation of the targets that must be maintained in working memory for the duration of the trial.…”
mentioning
confidence: 99%